2023
DOI: 10.1038/s41467-023-43592-6
|View full text |Cite
|
Sign up to set email alerts
|

Daily vocal exercise is necessary for peak performance singing in a songbird

Iris Adam,
Katharina Riebel,
Per Stål
et al.

Abstract: Vocal signals, including human speech and birdsong, are produced by complicated, precisely coordinated body movements, whose execution is fitness-determining in resource competition and mate choice. While the acquisition and maintenance of motor skills generally requires practice to develop and maintain both motor circuitry and muscle performance, it is unknown whether vocal muscles, like limb muscles, exhibit exercise-induced plasticity. Here, we show that juvenile and adult zebra finches (Taeniopygia castano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…Our results indicating that the long-term SS induces substantial changes in adult song structure and amplitude are largely consistent with the findings of a recent study by Adam et al 19 . Although they employed a different SS method, both our results and theirs lead to virtually the same conclusion.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results indicating that the long-term SS induces substantial changes in adult song structure and amplitude are largely consistent with the findings of a recent study by Adam et al 19 . Although they employed a different SS method, both our results and theirs lead to virtually the same conclusion.…”
Section: Discussionsupporting
confidence: 93%
“…Although they employed a different SS method, both our results and theirs lead to virtually the same conclusion. However, our study includes the following new findings that were not reported in Adam et al 19 : SS-induced song changes are mostly recovered within a short period of free singing, providing more direct evidence for the function of undirected singing in maintaining adult song performance; the recovery of song performance following the SS period does not necessarily require AF, revealing novel, AF-independent mechanisms for the maintenance of song performance; SS-induced song changes do not strongly depend on age, highly contrasting with AF-dependent song plasticity that has previously reported 16 , 17 . Because Adam et al 19 also reported the experimental findings that are not included in our current study, these two studies complement each other to significantly advance our understanding of the mechanisms by which adult birds maintain song performance through daily undirected singing.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations